(untitled) (Journal of Parents and Teachers, 2014)
This article talks about the process of making the portfolio and who makes it: a student, teacher or parents. It also includes what to add to the portfolio, the choice criteria that should have as teachers, students or parents to include in it and an example of a reading index card.